Synthesis and Spectral Characterization of Lanthanide Complexes Containing Bidentate Schiff Base Derived From Pyridine-2-Carbaldehyde and 2-Hydrazinylquinoline - Vaishali Ramesh Rajewar; M. K. Dharmale; S. R. Pingalkar (The Journal of Pure and Applied Chemistry Research, 2015)
A series of new rare earth complexes of La(III) of the type [Ln(L)2(H2O)2]Cl3 where Ln= La(III), Pr(III), Nd(III), Sm(III) and Tb(III) and L=Schiff base ligand, 2-[2-(pyridin-2-ylmethylidene)hydrazinyl]quinoline (PCQH). These complexes have been characterized on the basis of elemental analysis (Ln, C, H, N, and Cl), melting point, IR, 1H-NMR and UV-Vis spectral data. X-ray powder diffraction study of two of the complex [Nd(L)2(H2O)2]Cl3 and Pr(L)2(H2O)2]Cl3 was found to be on powder diffraction with Cu-K α1 radiation (λ = 1.5406 Å) showing monoclinic crystal system . The complexes were found to be coloured solid and were soluble only in DMF and DMSO.